2022
DOI: 10.3390/su14095428
|View full text |Cite
|
Sign up to set email alerts
|

Flipped Classroom and Gamification Approach: Its Impact on Performance and Academic Commitment on Sustainable Learning in Education

Abstract: The onset of the COVID-19 global pandemic has negatively impacted sustainable learning in education (SLE). During city lockdowns, higher education institutes (HEIs) have transitioned from adopting solely traditional didactic classroom teaching to including innovative, flexible learning approaches such as flipped classrooms. Gamification is a new techno-pedagogy that has been integrated into flipped classrooms to promote learner achievement and engagement. Grounded in self-determination theory, the objectives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 112 publications
0
18
0
Order By: Relevance
“…Conversely, in primary education we again highlight DLF (30.4%) as the most selected approach. Ng and Lo (2022) note that teachers tend to prefer interactive learning in class to self-regulated study prior to class. The authors found better learning performance in a traditional classroom approach supplemented by gamification, as teacher recognition and feedback in the form of game design elements were valued much higher.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in primary education we again highlight DLF (30.4%) as the most selected approach. Ng and Lo (2022) note that teachers tend to prefer interactive learning in class to self-regulated study prior to class. The authors found better learning performance in a traditional classroom approach supplemented by gamification, as teacher recognition and feedback in the form of game design elements were valued much higher.…”
Section: Discussionmentioning
confidence: 99%
“…Students who follow the flipped classroom model can take advantage of the flexible environment through independent learning and collaboration. Personal factors and behaviors that support this theory are considered before implementing the model (Ng & Lo, 2022).…”
Section: The Contradiction Of Supporting Learning Theory With the Imp...mentioning
confidence: 99%
“…COVID-19 has had a negative impact on sustainable education learning. Teachers must transition from traditional classroom teaching to innovative and flexible learning methods to improve learners' achievements and participation [48]. Based on the United Nations Sustainable Development Goal 4, "Achieving inclusive and high-quality education for all," and the above research conclusions, this paper, from the perspective of teachers' sustainable teaching and students' continuous learning, combined the specific manifestations of the three learning psychologies and proposed improvement measures to improve the three learning psychological states of college students in the context of the COVID-19 pandemic and promote the sustainable development of classroom teaching in the post-pandemic era.…”
Section: Improvement Measuresmentioning
confidence: 99%